Parameter Biologi dan Demografi Parasitoid Diadegma semiclausum Hellen (Hymenoptera : Ichneumonidae) pada Plutella xylostella L. (Lepidoptera : Plutellidae) - KUMARAWATI, NI PUTU NIA; SUPARTHA, I WAYAN; YULIADHI, KETUT AYU (Agrotrop : Journal on Agriculture Science; Vol 8 No 2 (2018)DO - 10.24843/AJoAS.2018.v08.i02.p06, 2019)
Biological and Demographic Parameters of Parasitoid Diadegma semiclausum Hellen (Hymenoptera: Ichneumonidae) on Plutella xylostella L. (Lepidoptera: Plutellidae). Diadegma semiclausum Hellen (Hymenoptera: Ichneumonidae) is one of the parasitoid larvae which attacks Plutella xylostella (Lepidoptera: Plutellidae) effectively. This research was aimed to know the biology of parasitoid D. semiclausum in broccoli. The research was carried out in a laboratory by observing the development of parasitoid, fecundity, longevity the males and females as well as parameters demographic of D. semiclausum . The results showed that immature development time of D. semiclausum parasitoid from egg up to adult the imago was 10.65 ± 0.63 days, with the number of fecundity was 22.9 grains. Longevity of male imago of D. semiclausum was 12.10 ± 0.74 days and imago of females 9.80 ± 1.87 days. Parameters demographic of D. semiclausum showed that net reproduction rate (R 0 ) was 22.11 per generation, intrinsic growth rate (r) was 0.18 per day, limited increased rate (?) was 1.16 individuals per day, generation time (T) was 17.50 day.